'It could never be just about beer': race, gender, and marked professional identity in the US craft beer industry. Issue 2 (5th April 2022) - Wilson, Eli R
Abstract: To critical observers, the growth and professionalization of the US craft beer industry over the last few decades has meant the expansion of yet another kind of workplace replete with standards of whiteness and masculinity. Yet the first-hand experiences of workers in this setting—one that values authenticity and features growing support for social inclusivity—remain understudied. This study asks how do women and people of color negotiate work identities in craft beer? Based on 56 in-depth interviews as well as ethnographic field research in US craft breweries, this study demonstrates how minoritized workers enact their work identities in ways that are both enabled and constrained by their workplace contexts. I find that women and people of color attempt to construct marked professional identities that adhere to existing standards of industry professionalism while selectively engaging their race and gender identities when it is advantageous to do so. I elaborate on how marked professional identities may especially resonate in organizational settings that prioritize authenticity and feature less entrenched organizational norms.